Prepare for ielts academic modules Các khối thi học thuật; Practice tests for Listening, Reading, Writing and Speaking in the test of the International English Language Testing System - Todd Vanessa (Thành phố Hồ Chí Minh, 2000)
Nghe nói đọc viết trong tiếng anh; các bài thi tiếng anh